Space charges analysis on insulator with uniform layer contamination effect - Mohd Haris Asyraf Shee Kandar; Nor Akmal Mohd Jamail; Qamarul Ezani Kamarudin; Nordiana Azlin Othman; Nor Asiah Muhamad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
High voltage direct current (HVDC) transmission provides an attractive alternative for bulk power transfer. However, HVDC transmission may have loss about half per unit length of high voltage alternating current (HVAC) at the same amount of power carried. This is due to the space charge formation around the conductor in HVDC cables. It is known that the presence of space charge inside an insulator may distort the local electric field and surface energy. This paper investigates the effect of electrostatics for space charge, electric field and surface energy in the HVDC cable in clean and contaminated conditions. The effect of uniform layer contamination from oil, sandstone and fresh water was conducted on 11 kV XLPE cable using finite element software under electrostatics study. The contamination layer was created around the XLPE cable by multifarious the radius of layer contamination from the conductor. The simulation results show that enlargement of contamination layer radius by 1.0 mm (light), 1.5 mm (medium) and 2.0 mm (heavy) resulted in the reduction of surface energy by 20% and electric field by 22% but increase the space charge amplitude by 76%. The study also found that fresh water can be considered as the worst contamination compared to oil and sandstone.